Impact of the Supervisor Feedback Environment on Creative Performance: A Moderated Mediation Model - Zhang, Jian; Gong, Zhenxing; Zhang, Shuangyu; Zhao, Yujia (Frontiers in Psychology, 2017)
Studies on the relationship between feedback and creative performance have only focused on the feedback-self and have underestimated the value of the feedback environment. Building on Self Determined Theory, the purpose of this article is to examine the relationship among feedback environment, creative personality, goal self-concordance and creative performance. Hierarchical regression analysis of a sample of 162 supervisor-employee dyads from 9 industry firms. The results indicate that supervisor feedback environment is positively related to creative performance, the relationship between the supervisor feedback environment and creative performance is mediated by goal self-concordance perfectly and moderated by creative personality significantly. The mediation effort of goal self-concordance is significantly influenced by creative personality. The implication of improving employees’ creative performance is further discussed. The present study advances several perspectives of previous studies, echoes recent suggestions that organizations interested in stimulating employee creativity might profitably focus on developing work contexts that support it.